Expression of clock gene Dbp in omental and mesenteric adipose tissue in patients with type 2 diabetes. Issue 1 (18th August 2020) - Ushijima, Kentaro; Suzuki, Chisato; Kitamura, Hiroko; Shimada, Ken; Kawata, Hirotoshi; Tanaka, Akira; Horie, Hisanaga; Hosoya, Yoshinori; Imai, Yasushi; Yamashita, Chikamasa; Fujimura, Akio
Abstract : Introduction: We previously reported in ob/ob mice, one of animal models of human type 2 diabetes mellitus (DM2), that (i) acetylation of histone H3 lysine 9 (H3K9) at the promoter region of clock gene Dbp and DBP mRNA expression are reduced in epididymal adipose tissue, (ii) binding of DBP to the promoter region of peroxisome proliferator-activated receptor ( Ppar)-γ and mRNA expression of PPAR-γ1sv were decreased in preadipocytes and (iii) adiponectin secretion was decreased, leading to the impaired insulin sensitivity. Research design and methods: The present study was undertaken to evaluate whether such the changes in visceral adipose tissue were detected in patients with DM2. We obtained omental and mesenteric adipose tissue during surgery of lymph node dissection for gastric and colorectal cancers, and investigated these variables in adipose tissue (omental from gastric cancer; 13 non-DM, 12 DM2: mesenteric from colorectal cancer; 12 non-DM, 11 DM2). Results: Acetylation of histone H3K9 at the promoter region of Dbp and DBP mRNA expression in omental, but not in mesenteric adipose tissue were significantly lower in DM2 than in patients without DM. PPAR-γ mRNA expression in omental adipose tissue was also lower in patients with DM2, but not in mesenteric adipose tissue. Conclusions: The changes in DBP-PPAR-γ axis observed in mice with diabetes were also detected in patients with DM2. Because adiponectin secretion is reported to be enhanced through the PPAR-γ-related mechanism, this study supports the hypothesis that omental adipose tissue is involved in the mechanism of DM2.